Carbonate and silice discrimination using thermal infrared bands - Villanueva Núñez, Robinson Ernesto (2007)
Nowadays, the Remote Sensing like scientific activity, related to Earth Sciences, has been constituted in a useful and profitable tool in the technological and industrial tasks, offering valuable information for diverse applications. One of them and that we will insist on this investigation is to identify carbonates, silica. By the nature of the study we will use sensors that have several bands in the thermal infrared, by the availability of the information and cost, initially we will use the data ASTER.